Acceptability of a standalone written leaflet for the National Health Service for England Targeted Lung Health Check Programme: A concurrent, think‐aloud study - Mbasan Jallow; Georgia Black; Sandra vanOs; David R. Baldwin; Kate E. Brain; Michael Donnelly; Samuel M. Janes; Clara Kurtidu; Grace McCutchan; Kathryn A. Robb; Mamta Ruparel; Samantha L. Quaife (Wiley, 2022)
Abstract Background Many countries are introducing low‐dose computed tomography screening programmes for people at high risk of lung cancer. Effective communication strategies that convey risks and benefits, including unfamiliar concepts and outcome probabilities based on population risk, are critical to achieving informed choice and mitigating inequalities in uptake. Methods This study investigated the acceptability of an aspect of NHS England's communication strategy in the form of a leaflet that was used to invite and inform eligible adults about the Targeted Lung Health Check (TLHC) programme. Acceptability was assessed in terms of how individuals engaged with, comprehended and responded to the leaflet. Semi‐structured, 'think aloud' interviews were conducted remotely with 40 UK screening‐naïve current and former smokers (aged 55-73). The verbatim transcripts were analysed thematically using a coding framework based on the Dual Process Theory of cognition. Results The leaflet helped participants understand the principles and procedures of screening and fostered cautiously favourable intentions. Three themes captured the main results of the data analysis: (1) Response-participants experienced anxiety about screening results and further investigations, but the involvement of specialist healthcare professionals was reassuring; (2) Engagement-participants were rapidly drawn to information about lung cancer prevalence, and benefits of screening, but deliberated slowly about early diagnosis, risks of screening and less familiar symptoms of lung cancer; (3) Comprehension-participants understood the main principles of the TLHC programme, but some were confused by its rationale and eligibility criteria. Radiation risks, abnormal screening results and numerical probabilities of screening outcomes were hard to understand. Conclusion The TLHC information leaflet appeared to be acceptable to the target population. There is scope to improve aspects of comprehension and engagement in ways that would support informed choice as a distributed process in lung cancer screening. Patient or Public Contribution The insight and perspectives of patient representatives directly informed and improved the design and conduct of this study.